2017
DOI: 10.1108/gm-02-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

The relational expectations of women managing women

Abstract: Purpose The purpose of this paper is to examine the expectations women have of their women managers and/or women employees and to suggest personal and organizational strategies to strengthen those relationships. Design/methodology/approach Building on a first phase of research using narrative inquiry into the lived experiences of women managing and/or being managed by women, workshops were held with 13 participants to explore their relationship expectations of women managers and/or employees. Findings Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Gendered expectations related to empathy and female coaches in this study echoes Hurst et al's (2017) findings of relational expectations placed on female managers in a variety of occupational settings. More specifically, in Hurst et al's study, women held higher relational expectations for other women, and when those expectation were not met, female managers suffered strained relationships or other relational penalties.…”
Section: Empathysupporting
confidence: 73%
See 1 more Smart Citation
“…Gendered expectations related to empathy and female coaches in this study echoes Hurst et al's (2017) findings of relational expectations placed on female managers in a variety of occupational settings. More specifically, in Hurst et al's study, women held higher relational expectations for other women, and when those expectation were not met, female managers suffered strained relationships or other relational penalties.…”
Section: Empathysupporting
confidence: 73%
“…However, women who expressed masculinities too openly were also penalized and excluded from senior management because of these behaviors. Hurst, Leberman, and Edwards (2017) recently found that women in a variety of occupational settings have higher relational expectations of their female managers compared to their male managers in terms of emotional understanding and support. They also found that relationships between female employee and female manager were strained when the relational expectations were not met.…”
Section: Agencymentioning
confidence: 99%
“…Interestingly, the male respondents mentioned task-related aspects more often than the female respondents, who in turn emphasised more relational aspects. This finding illustrates the subtle impact of the gender of respondents on their perceptions of what they would look for in protégés and reinforces the gender-based expectations of protégés, in line with Hurst et al (2017) prior research findings. Organisations would benefit from taking note of how gender influences perceptions of merit and genderbased expectations.…”
Section: Theme 2: Sponsoring Otherssupporting
confidence: 87%
“…In cases where the sponsor and protégé, or mentor and protégé, are the same gender, particularly female, the protégé may have high expectations with regards to the relational competence of the sponsor or mentor. A recent study by Hurst, Leberman and Edwards (2017) reveals that while participants initially believed they expected the same things of managers or employees, irrespective of gender, a deeper investigation uncovered gender-based expectations. For example, women expected more emotional support from someone of the same gender.…”
Section: Challenges Of Sponsorship or Mentoringmentioning
confidence: 99%
See 1 more Smart Citation